Mandible vertical height correction using lingual bone-split pedicle onlay graft technique - Coen Pramono D (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
As edentulous mandible become atrophic, a denture bearing area will also be reduced. Difficulty in the removable prosthesis rehabilitation will be present as well. The purpose of this paper reports an innovative surgical technique to cope a problem of unstable complete lower denture due to bone atrophy and resulted of vertical height reduction of the anterior region of the mandible necessary for denture retention. Vertical advancement of the lower jaw using lingual bone split pedicle onlay graft technique in the anterior region of the mandible and followed by secondary epithelization vestibuloplasty in achieving the vertical height dimension. The surgery was achieved satisfactorily as the vertical dimension of the mandible anterior region had increased and the denture seated more stable comparing with the previous denture worn by the patient. It concluded that the surgery was achieved with a great result as the vertical height of the anterior region of the mandible had increased positively therefore lead the denture seated more stable.